Berlyne Revisited: Evidence for the Multifaceted Nature of Hedonic Tone in the Appreciation of Paintings and Music - Marin, Manuela M.; Lampatz, Allegra; Wandl, Michaela; Leder, Helmut (Frontiers in Human Neuroscience, 2016)
In his seminal book on aesthetics, Berlyne (1971) posited an inverted-U relationship between complexity and hedonic tone in arts appreciation, however, converging evidence for his theory is still missing. The disregard of the multidimensionality of complexity may explain some of the divergent results. Here, we argue that definitions of hedonic tone are manifold and systematically examined whether the nature of the relationship between complexity and hedonic tone is determined by the specific measure of hedonic tone. In Experiment 1, we studied three picture categories with similar affective and semantic contents: 96 affective environmental scenes, which were also converted into 96 cartoons, and 96 representational paintings. Complexity varied along the dimension of elements. In a between-subjects design, each stimulus was presented for 5 s to 206 female participants. Subjective ratings of hedonic tone (either beauty, pleasantness or liking), arousal, complexity and familiarity were collected in three conditions per stimulus set. Complexity and arousal were positively associated in all conditions, with the strongest association observed for paintings. For environmental scenes and cartoons, there was no significant association between complexity and hedonic tone, and the three measures of hedonic tone were highly correlated (all rs >.85). As predicted, in paintings the measures of hedonic tone were less strongly correlated (all rs >.73), and when controlling for familiarity, the association with complexity was significantly positive for beauty (rs = .26), weakly negative for pleasantness (rs = -.16) and not present for liking. Experiment 2 followed a similar approach and 77 female participants, all non-musicians, rated 92 musical excerpts (15 s) in three conditions of hedonic tone (either beauty, pleasantness or liking). Results indicated a strong relationship between complexity and arousal (all rs >.85). When controlling for familiarity effects, the relationship between complexity and beauty followed an inverted-U curve, whereas the relationship between complexity and pleasantness was negative (rs = -.26) and the one between complexity and liking positive (rs = .29). We relate our results to Berlyne’s theory and to the latest findings in neuroaesthetics, proposing that future studies need to acknowledge the multifaceted nature of hedonic tone in aesthetic experiences of artforms.